Short Communication: Altitudinal distribution of Papilionoidea (Lepidoptera) in Mount Aragats, Armenia - NOUSHIG ZARIKIAN (Biodiversitas Journal of Biological Diversity, 2017)
Zarikian N. 2017. Altitudinal distribution of Papilionoidea (Lepidoptera) in Mount Aragats, Armenia. Biodiversitas 18: 818- 825. In this study, the altitudinal distribution of butterflies on the highest mountain in Armenia was investigated. Butterflies were collected from March to October in 2015 and 2016. This revealed that the relationship between the total numbers of butterfly species and individuals and altitude shaped as bump. A significant relationship was also recorded between the altitude and the abundance and richness. However, the diversity and evenness index yielded a consistent decrease with increase in altitude because of the dominance of few species at high altitudes